2022
DOI: 10.1161/circep.121.010744
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Implantable Electronic Devices in Ebstein Anomaly: Management and Outcomes

Abstract: Background: Optimal management of cardiac implantable electronic devices (CIEDs) in patients with Ebstein anomaly during tricuspid valve (TV) surgery is unknown. Thus, we aimed to characterize CIED management/outcomes in patients with Ebstein anomaly undergoing TV surgery. Methods: Patients at the Mayo Clinic from 1987 to 2020 with Ebstein anomaly and CIED procedure were reviewed for procedural details, complications, echocardiogram, and lead parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[129][130][131] However, electronic pacemakers have been associated with several drawbacks, including electrochemical reactions at the electrode tissue interface, invasive surgery, repeated battery replacement, infection risk, and equipment failure. [132][133][134][135][136] Optogenetic technology, which involves transmitting various opsins to the heart through viral vectors and controlling heart rate through depolarization or repolarization stimulation, presents a promising alternative to electronic pacemakers. 137,138 Research has demonstrated that pacing the heart at multiple sites reduces activation time, thus leading to highly synchronized ventricular activation through the fusion of multiple wave fronts generated simultaneously by all chr2 expression sites.…”
Section: Genetic and Heart Light Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…[129][130][131] However, electronic pacemakers have been associated with several drawbacks, including electrochemical reactions at the electrode tissue interface, invasive surgery, repeated battery replacement, infection risk, and equipment failure. [132][133][134][135][136] Optogenetic technology, which involves transmitting various opsins to the heart through viral vectors and controlling heart rate through depolarization or repolarization stimulation, presents a promising alternative to electronic pacemakers. 137,138 Research has demonstrated that pacing the heart at multiple sites reduces activation time, thus leading to highly synchronized ventricular activation through the fusion of multiple wave fronts generated simultaneously by all chr2 expression sites.…”
Section: Genetic and Heart Light Systemmentioning
confidence: 99%
“…In the clinical management of chronic arrhythmia and heart failure due to different ventricular pacings, the electronic pacemaker has been the predominant treatment 129–131 . However, electronic pacemakers have been associated with several drawbacks, including electrochemical reactions at the electrode tissue interface, invasive surgery, repeated battery replacement, infection risk, and equipment failure 132–136 . Optogenetic technology, which involves transmitting various opsins to the heart through viral vectors and controlling heart rate through depolarization or repolarization stimulation, presents a promising alternative to electronic pacemakers 137,138 .…”
Section: Applications Of Optogenetics In Various Fieldsmentioning
confidence: 99%